Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews - Abramov, Alexei V.; Bannikova, Anna A.; Lebedev, Vladimir S.; Rozhnov, Viatcheslav V. (Zootaxa, 2017)
We analyzed the complete mitochondrial cytochrome b (cytb) gene and fragments of four nuclear loci: ApoB, RAG2, IRBP1 and BRCA1. These data allowed us to provide new insights into the diversity of the Asiatic water shrews of Indochina. A new, highly divergent genetic lineage of Chimarrogale was found in southern Vietnam, and this lineage included specimens from the provinces of Kon Tum, Dak Lak, and Lam Dong. Such finding represents the newest and southernmost records of Chimarrogale in Indochina. Morphological analysis classified the specimens from southern Vietnam as C. varennei proper, which is restricted to that region, whereas the polymorphic C. himalayica, which contained at least four cytochrome b haplogroups, occurred in central and northern Vietnam and southern China. This distinct C. varennei lineage closely related to the C. platycephalus + C. leander clade suggests the existence of an unknown glacial refuge in Tay Nguyen Plateau, southern Vietnam. Because the Bornean C. phaeura (i) was sister-group of the rest of Chimarrogale sensu lato and (ii) had a high genetic divergence ( 15% for cytochrome b) and geographical isolation, we suggest that C. phaeura be placed into a separate genus, Crossogale Thomas, 1921. This genus should also include C. sumatrana (Sumatra) and C. hantu (Peninsular Malaysia). On those grounds, we propose a new classification system for Asiatic water shrews.